2016
DOI: 10.1016/j.neuroscience.2016.01.005
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms mediating nitroglycerin-induced delayed-onset hyperalgesia in the rat

Abstract: Nitroglycerin (glycerol trinitrate, GTN) induces headache in migraineurs, an effect that has been used both diagnostically and in the study of the pathophysiology of this neurovascular pain syndrome. An important feature of this headache is a delay from the administration of GTN to headache onset that, because of GTN’s very rapid metabolism, cannot be due to its pharmacokinetic profile. It has recently been suggested that activation of perivascular mast cells, which has been implicated in the pathophysiology o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
30
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(32 citation statements)
references
References 75 publications
2
30
0
Order By: Relevance
“…Similar incomplete effects were reported for amiloride in another rat migraine model with a direct dural acidic stimulation (Yan et al ., ) and in a mice NTG‐induced model of chronic migraine (Tipton et al ., ). The complete reversibility of cephalic allodynia by ASIC1 inhibitors that we observed would suggest that sensitization of the TNC and the upper cervical dorsal horn could depend directly on the activity of TG sensory neurons expressing ASIC1‐containing channels, whereas extra‐cephalic allodynia would be partially independent of them, involving central mechanisms independent of TG fibres activation (Bernstein and Burstein, ) or ASIC‐independent effects of NO on paw sensory fibres (Ferrari et al ., ).…”
Section: Discussionmentioning
confidence: 97%
“…Similar incomplete effects were reported for amiloride in another rat migraine model with a direct dural acidic stimulation (Yan et al ., ) and in a mice NTG‐induced model of chronic migraine (Tipton et al ., ). The complete reversibility of cephalic allodynia by ASIC1 inhibitors that we observed would suggest that sensitization of the TNC and the upper cervical dorsal horn could depend directly on the activity of TG sensory neurons expressing ASIC1‐containing channels, whereas extra‐cephalic allodynia would be partially independent of them, involving central mechanisms independent of TG fibres activation (Bernstein and Burstein, ) or ASIC‐independent effects of NO on paw sensory fibres (Ferrari et al ., ).…”
Section: Discussionmentioning
confidence: 97%
“…This latter study also showed that blockade of ERK phosphorylation inhibited NTG-mediated afferent sensitization. Further, new data from Levine and colleagues implicate a role for mast cells and endothelial cells in NTG-induced hyperalgesia (Ferrari et al, 2016). The activation of purinergic receptors on endothelial cells also stimulates proflammatory pathways (Erlinge and Burnstock, 2008) including the release of interleukins (Seiffert et al, 2006) known to sensitize meningeal afferents (Zhang et al, 201; Yan et al, 2012).…”
Section: 1 Meningeal Afferentsmentioning
confidence: 99%
“…2 Consequently, the experimental migraine induced by nitroglycerin (NTG) administration (an NO donor) is one of the most reliable experimental models for migraine inducement in rats. 3 NTG-induced hyperalgesia can be evaluated by assessment of the nociceptive behavior evoked by the formalin test. 2 Common migraine triggers are capable of generating oxidative stress, and oxidative-stress molecules released during migraine attack can contribute to nociceptive mechanism.…”
Section: Introductionmentioning
confidence: 99%